2018
DOI: 10.3390/ma11060874
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dynamic Recrystallization on Monotonic and Cyclic Behaviour of Al-Cu-Mg Alloy

Abstract: The paper presents an investigation that was conducted to determine the possibility of the occurrence of the process of dynamic recrystallization in 2024 alloy during monotonic tensile and creep tests at the elevated temperatures of 100 °C, 200 °C, and 300 °C. As-extruded material was subjected to creep process with constant force at elevated temperatures, until two varying degrees of deformation were reached. After cooling at ambient temperature, the pre-deformed material was subjected to monotonic and fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Moreover, the selected area electron diffraction (SAED) exhibited a clear ring-like pattern, which is consistent with the EBSD results. Hence, based on the obvious grain boundaries and low dislocation density, it can be concluded that some ultra-fine grains contain typical dynamically recrystallized grains, which was in agreement with the results of Tomczyl et al [ 18 ].…”
Section: Resultssupporting
confidence: 91%
“…Moreover, the selected area electron diffraction (SAED) exhibited a clear ring-like pattern, which is consistent with the EBSD results. Hence, based on the obvious grain boundaries and low dislocation density, it can be concluded that some ultra-fine grains contain typical dynamically recrystallized grains, which was in agreement with the results of Tomczyl et al [ 18 ].…”
Section: Resultssupporting
confidence: 91%
“…It is likely that the recrystallization effect is dependent on recrystallization grain microstructures and testing conditions. A study on the Al-Cu-Mg alloy showed that dynamic recrystallization can increase fatigue life in the plastic region and decrease it in elastic region, with recrystallization occurring in the entire sample [14]. To simulate the actual recrystallization microstructure in turbine blades, i.e., discrete recrystallized grains, local recrystallization was specially prepared in this work, using indentation and annealing instead of continuous recrystallized grains/layer as used in most studies [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These include Young’s modulus E and tensile strength σ c as well as parameters K and n of the Ramberg–Osgood equation [ 54 ]: where σ and ε are the stress and the corresponding strain, and ε e and ε p are the elastic and plastic strains. These material characteristics were determined based on the monotonic tensile tests at 100, 200 and 300 °C [ 52 , 55 , 56 ] and are summarized in Table 1 . It should be emphasized that the monotonic tensile tests were carried out for three samples at each temperature, and their results were averaged.…”
Section: Test Stand Materials Characteristic Samplesmentioning
confidence: 99%